Factors Affecting Speaking Proficiency in English Language Learning: A general overview of the speaking skill - Zanyar Nathir Ghafar; Bareq Raad Raheem (Al-Makki Publisher, 2023)
For effective communication, speaking abilities must be developed and improved. One of the most complicated aspects of learning a new language is gaining speaking proficiency, which is commonly considered difficult. Many people learning a language encounter difficulties expressing their ideas and thoughts verbally. Individuals frequently need help with expressing themselves clearly in a foreign language. Individuals cease verbal communication when they encounter psychological obstacles or exhaust their repertoire of suitable linguistic formulations. Proficiency in spoken English is a vital requirement in today's modern communication and media landscape. This study aims to illustrate the significance of focusing on the factors that impact the speaking proficiency of those learning English as a second language. This review paper provides an overview of the existing body of research on speaking, its significance, the features of speaking performance, difficulties related to speaking, and factors that can influence speaking performance. The literature review indicated that learners prioritize and require increased attention to effective instruction in speaking skills. The findings of this study have the potential to inform educators and researchers about the speaking demands that English language learners face within the domain of English language instruction and acquisition.